Analysis of Constitutional Court Decision No. 30/Puu-Xvi/2018 and Supreme Court Decision No. 65p/Hum/2018 Concerning the Prohibition of Concurrent Positions for Regional Representative Council Candidates (DPD) - Riswan Rais Syarif; Sultan Alwan; Rudhi Achsoni (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to examine the differences between the Constitutional Court's decision and the Supreme Court's decision regarding the prohibition of concurrent positions as candidates for members of DPD, as well as the legal ramifications of these differences. This research employs the normative legal research approach, which refers to legal research that refers to written regulations or other legal materials. Disparity between the Constitutional Court Decision and the Supreme Court is the different time for enforcing the ban on candidates for DPD members from political party officials, according to the findings of this study. The Constitutional Court stated that it has been in effect since the 2019 election, however the Supreme Court stated since after the 2019 election. This disparity or difference may be caused by several factors, including: the Constitutional Court's and the Supreme Court's different authorities when examining a statutory regulation; the Constitutional Court's and the Supreme Court's use of different touchstones when examining a statutory regulation; and the judges of the Constitutional Court and the Supreme Court's differing perspectives when analyzing cases. The absence of legal certainty and the violation of citizens' constitutional rights are the legal consequences of the gap between the two judgements.